2016
DOI: 10.18632/oncotarget.8745
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic features of lung squamous cell cancer in never-smokers

Abstract: To evaluate the importance of specific driver mutations to the development and outcome of lung squamous cell cancer (SQCC) in never-smokers, we assessed the clinicopathological characteristics and outcomes of 597 patients who underwent complete resection of SQCCs. In total, 88 (14.7%) never-smokers and 509 (85.3%) ever-smokers were compared. The never-smokers included more females (42.05% vs. 1.57%, P < 0.001) and more often had a personal history of malignant disease (9.09% vs. 2.36%, P = 0.003). The tumors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 29 publications
5
24
0
Order By: Relevance
“…The overrepresentation of women in this group is also confirmed [7][8][9][10][11][12][14][15][16][17][18][20][21][22]24,26], and supports the notion of the presence of sex-based differences either in vulnerability to non-tobacco associated lung cancer or in exposure to other risk factors, such as environmental tobacco smoke. Due to observed sex imbalances, there has been considerable interest surrounding the possible role of oestrogen [6,9,34,35].…”
Section: Patient Characteristicssupporting
confidence: 72%
See 2 more Smart Citations
“…The overrepresentation of women in this group is also confirmed [7][8][9][10][11][12][14][15][16][17][18][20][21][22]24,26], and supports the notion of the presence of sex-based differences either in vulnerability to non-tobacco associated lung cancer or in exposure to other risk factors, such as environmental tobacco smoke. Due to observed sex imbalances, there has been considerable interest surrounding the possible role of oestrogen [6,9,34,35].…”
Section: Patient Characteristicssupporting
confidence: 72%
“…The observed higher proportion of both younger (<50 years) and older patients (80 years) among never-smoking has, to the best of our knowledge, never been observed before. However, there have also been reports of no differences in age and also the opposite, i.e., a younger age at diagnosis among never-smokers [7][8][9][10]14,15,[17][18][19][20][21][22]26]. None of the studies reporting an older age for never-smokers included an East Asian population.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with LUAD, patients with SCC in East Asian are the most suitable population for immunotherapy. Our previous study has shown that SCC in China are characterized by high proportion of never smoker, compared with the reported data of TCGA project from West SCC patients (18)(19)(20). This difference may add to the explanation of relatively low PD-L1 expression in East Asian SCC patients.…”
Section: Discussionmentioning
confidence: 84%
“…[20][21][22] We did not identify any EGFR mutations in the SCCs or LCNECs included in our study. However, both tumor types showed potential therapeutic targets such as mutations in MET and RET genes.…”
Section: Discussionmentioning
confidence: 99%